Generalized Closed Sets with Respect to an Ideal (European Journal of Pure and Applied Mathematics, 2011)
An ideal on a set X is a non empty collection of subsets of X with heredity property which is also closed under finite unions. The concept of generalized closed sets was introduced by Levine. In this paper, we introduce and investigate the concept of generalized closed sets with respect to an ideal.